PENGARUH KONFLIK PERAN GANDA DAN STRESS KERJA TERHADAP KINERJA PEGAWAI WANITA FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS LAMBUNG MANGKURAT BANJARMASIN - Nora Pertiwi; Emy Rahmawati; Setio Utomo (Universitas Lambung Mangkurat, 2020)
Higher education is one of the pillars that functions as an institution that produces quality human resources (HR). An important element in moving the wheels of a college is the lecturer. The performance of lecturers from a tertiary institution can be elaborated and realized towards improving the performance of lecturers who support the development of the goals of higher education. In carrying out the Tri Dharma of Higher Education, lecturers are also assisted by staff called the Pramubakti / Contract Staff. In carrying out their duties as employees (lecturers or staff) who are married, there are indications of multiple roles, namely as a wife, mother and household manager and as a workforce.This study aims to examine the Effect of Dual Role Conflict (Job-Family (X1) - Family Job (X2)) and Job Stress (X3) Against Employee Performance (Y) Women in the Faculty of Social and Political Sciences, Lambung Mangkurat University Banjarmasin both partially or simultaneous. The samples taken were 36 people, namely married female employees (administrative staff) using a saturated sampling technique. Data collection using questionnaires while data analysis using Multiple Linear Regression Analysis through SPSS version 23 program.The test results prove that the Work-Family Conflict (X1) has a significant effect on female employee performance partially with the influence of 75.4% including the very strong category, Family-Work Conflict (X2) has a significant effect on female employee performance partially with a influence of 48.9% including the fairly strong category, Job Stress (X3) has a significant effect on female employee performance partially with a influence of 25.4% including a fairly strong category, while simultaneously Job-Family Conflict (X1), Family-Job Conflict (X2) and Job Stress (X3) has a significant effect on Employee Performance (Y) for women of 72.5% including the very strong category while the remaining 27.5% is influenced by other variables not found in this research model.Keywords: Dual Role Conflict, Job Stress, and Employee Performance